2014
DOI: 10.1038/srep04300
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Xenorhabdusnematophila TB on plant pathogens Phytophthora capsici and Botrytis cinerea in vitro and in planta

Abstract: Entomopathogenic bacteria Xenorhabdus spp. produce secondary metabolites with potential antimicrobial activity for use in agricultural productions. This study evaluated the inhibitory effect of X. nematophila TB culture on plant pathogens Botrytis cinerea and Phytophthora capsici. The cell-free filtrate of TB culture showed strong inhibitory effects (>90%) on mycelial growth of both pathogens. The methanol-extracted bioactive compounds (methanol extract) of TB culture also had strong inhibitory effects on myce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 33 publications
0
35
0
4
Order By: Relevance
“…In vivo efficiencies of the methanol extracts of the wild‐type and ΔcpxR strain against B. cinerea were determined on tomato fruits according to the previously described methods (Fang et al., ). To determine the therapeutic effect, three tomato fruits with the similar size were placed at the bottom of a closed plastic container with moisture filter papers at the bottom to maintain high humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo efficiencies of the methanol extracts of the wild‐type and ΔcpxR strain against B. cinerea were determined on tomato fruits according to the previously described methods (Fang et al., ). To determine the therapeutic effect, three tomato fruits with the similar size were placed at the bottom of a closed plastic container with moisture filter papers at the bottom to maintain high humidity.…”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was collected and stored at 4°C until use. The methanol extract of the cell-free culture was prepared according to previous methods (Boszormenyi et al, 2009;Fang, Li, Wang, & Zhang, 2011;Fang, Zhang, Tang, Wang, & Zhang, 2014). Briefly, cell-free filtrates (500 ml) of the ΔcpxR mutant and the wild type were mixed, respectively, with activated D101 polymeric adsorbent resin at 1:20 (v/v) and incubated for 24 hr.…”
Section: Cell-free Filtrate and Methanol Extract Preparationmentioning
confidence: 99%
“…These chemical compounds might produce changes in the composition of the rhizosphere (Webster, 2000), that negatively affects the soil community De Nardo, Grewal, McCartney, & Stinner, 2006;Han & Ehlers, 1999;Maxwell, Chen, Webster, & Dunphy, 1994;Ng & Webster, 1997). However, a recent study has explored this negative impact as a possible mechanism of control of other plant pathogens (Fang, Zhang, Tang, Wang, & Zhang, 2014). From a "vertebrate" perspective, this impact can be considerdd very limited.…”
Section: Impact On Non-target Organisms: Bacteriamentioning
confidence: 99%
“…It was found that about 6% of genome is involved in secondary metabolite production [9] which is more than that of Streptomyces. Entomopathogenic nematodes are known for their antibacterial activity [10,11], antifungal activity [12][13][14], nematicidal activity [15,16], insecticidal activity [17] and cytotoxicity against various cell lines [18]. This study mainly aims at isolation and identification of bioactive molecules produced by entomopathogenic bacteria associated with a nematode strain NL among the collection of 65 entomopathogenic nematode isolates maintained at the CTCRI laboratory and its activity against fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%